The scholarly impact of the most cited and award winner articles in International Business - Ferreira, Manuel Portugal; Ribeiro, Martinho Almeida; Serra, Fernando Ribeiro; Armagan, Sungu (Internext, 2015)
The knowledge and evolution of a discipline are supported on multiple contributions of scholars through their research, but some works have a larger impact on the field. In this paper we examine the most cited articles in international business (IB) research. Methodologically, we identify the six most cited articles published on the top journal for IB studies - Journal of International Business Studies (JIBS) -, which are also those prized with the ‘JIBS decade award’. This award symbolizes their contribution to the field. We assess the impact of the top six articles measuring citations in a sample of other top twelve business / management journals. The procedures of analyses involve counting citations and the co-citations networks of each of the six award winning articles to observe how widespread is their influence into domains that are outside the immediate boundaries of the theme researched in each article.